Herbert Hamilton Kelly S.S.M., 1860-1950: a study in failure: a contribution to the search for a credible Catholicism - Jones, Alan William (1971)
Taken from the Introduction: "Catholicism": What is it? Our title implies that it is not easily definable ... Herbert Kelly would have eschewed the word Catholicism and substituted the word Catholicity. Catholicism suggested to him a neatly ordered man-made system, coercive and repressive; in the deepest sense, a Godless thing. Catholicity, on the other hand, suggested to Kelly something quite different. He claimed that the word, Catholicity, properly understood, can be used appropriately only with regard to God, and never with regard to particular churches or individuals. It is one of those words which emphasises the universality, sovereignty and initiative of God. This is why we have chosen the word Catholicism in the title, not because we subscribe to Kelly's negative understanding of the word, but because we are primarily concerned with a particular man, his beliefs and opinions, and not with Almighty God. No doubt with a man like Herbert Kelly the question of God figures largely in the picture but He cannot be our starting point. We shall try to trace Herbert Kelly's attempt to find a "credible Catholicism". The route is a long and difficult one, involving an exploration into the personality and life of an extraordinary man who could be saintly yet childish; pelucid yet obtuse in almost everything he said, and wrote ...